AFRICAN STEREOTYPES IN AMERICAN TEEN MOVIE MEAN GIRLS - Fiza Asri Fauziah Habibah; Fadilah Fadilah (Universitas Nasional, 2022)
Movie has emerged to be a powerful device in shaping perspectives of culture, society and history. The power of visual stimulation can be manifested and exploited politically, socially and economically. The movie Mean Girls, which premiered in the United States in 2004 actualized the racial stereotypes lobbed at Africans, but with a soft ignorance. The present study aims to observe African stereotypes in American teen movie Mean Girl. This study employed qualitative descriptive method, which is a method of research that attempt to describe and interpret the objects in accordance with reality. The data of this study were collected from scenes and excerpts which contained African stereotypes based on its scripts. The study draws on Doh’s (2009) Stereotyping Africa: surprising answers to surprising questions and February (2019) Mind your colour: The “coloured” stereotype in South African literature. Findings have shown that the African stereotypes are black-skin coloured, wild and savage, financially poor, doing voodoo, and having impolite attitude. These stereotypes indicate the movie Mean Girls tends to perpetuate negative stereotypes about Africans more than the positive ones.Keywords: African stereotype; American teen movie; Mean Girls’s movie